Catalytic system for preparing cycloolefin copolymer and application
By using a catalyst system such as silane-bridged fluorenylamine dimethyl titanium, combined with appropriate cocatalysts and chain transfer agents, the problem of medium-chain transfer of cycloolefin copolymers is solved, and an efficient and controllable polymerization process is achieved.
Patent Information
- Application Number
- CN202510188749.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-02-20
AI Technical Summary
During the preparation of existing cycloolefin copolymers, it is difficult to select chain transfer agents reasonably, resulting in problems such as reduced catalyst activity and uneven molecular weight distribution.
A bridged monometallocene catalyst system such as fluorenylamine dimethyl titanium, is adopted to form an efficient catalytic system, combining aluminum compound or boron compound cocatalyst and a second main/subgroup metal complex chain transfer agent.
The polymerization activity is significantly improved, the molecular weight distribution is controlled, and the wide range of molecular weight adjustment and controllable cycloolefin insertion rate and glass transition temperature are achieved.
Smart Images

Figure CN119638892A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-performance polyolefins and relates to a catalytic system for preparing cycloolefin copolymers and application thereof. Background Art
[0002] Cyclic olefin copolymer (COC) is an amorphous thermoplastic polymer material with high light transmittance, high refractive index, low birefringence, low water absorption, light specific gravity, excellent thermal stability and low dielectric constant. It is widely used in optics, medicine, packaging and electrical appliances. It is considered to be an ideal substitute for PC, PS, PVC, PMMA and some engineering plastics. It can be used to manufacture optical lenses, films, optical fibers, medical devices, pharmaceutical packaging, bone materials, bipolar plate materials, etc. At present, the commercial COC products are mainly the Topas series of Polyplastics of Japan and the APEL series of Mitsui Chemicals of Japan.
[0003] COC is mainly prepared by the addition polymerization of α-olefins and cycloolefins catalyzed by metallocene catalysts. For example, in the literature (Macromolecules, 2011, 44(7): 1986-1998.), single metallocene complexes with different substituents were synthesized to achieve the copolymerization of α-olefins and cycloolefins, and the effect of metallocene catalysts with different structures on the copolymerization reaction was explored.
[0004] The polymerization mechanism initiated by the metallocene catalytic system is similar to that of the Ziegler-Natta system, that is, the coordination of olefin molecules and transition metals. The coordination polymerization mechanism usually consists of four elementary reactions: chain initiation, chain growth, chain transfer, and chain termination. Among them, chain transfer mainly includes β-H elimination and chain transfer to alkyl metals. However, metallocene catalysts generally have the disadvantage of "active polymerization", that is, it is difficult for the existing metallocene catalytic system to undergo chain transfer reaction. Each active center can only generate one active chain and continue to grow, which ultimately makes the molecular weight of the polymerization product too high and not conducive to processing, and the catalyst system has low initiation efficiency.
[0005] To solve the above problems, researchers usually add chain transfer agents, such as alkyl aluminum, alkyl zinc, alkyl magnesium, etc., to the polymerization system. The addition of chain transfer agents can significantly increase the chain transfer rate during the polymerization process, allowing each active center to grow multiple active chains, significantly reducing the consumption of expensive metallocene catalysts and controlling the molecular weight of the polymer. The chain transfer process determines the later processing and application conditions of the polymer, and is therefore a key factor in measuring whether the catalyst can be industrialized. However, the current reasonable selection of chain transfer agents in the preparation of cycloolefin copolymers is difficult. The difficulty lies in the fact that chain transfer reactions can only occur when the end of the growing active chain is a non-cyclic olefin, otherwise it cannot occur if the end is a cycloolefin. Therefore, the type and amount of the catalyst and chain transfer agent need to be highly matched and coordinated, otherwise it will affect the activity of the catalyst, the molecular weight and molecular weight distribution of the polymer, etc.
[0006] In the prior art, although attempts have been made to regulate the molecular weight of COC by adding chain transfer agents, the addition of chain transfer agents will significantly reduce the polymerization activity, and there are the disadvantages of a narrow range of regulated molecular weight and a wide molecular weight distribution. For example, patent CN201710928754 discloses a method for preparing COC, and an alkyl aluminum compound chain transfer agent is added to the metallocene catalyst system to control the molecular weight of COC. The disadvantage is that the molecular weight of the polymer decreases while causing a sharp increase in the width of the molecular weight distribution. Patent CN202110171214 discloses a polymerization method for efficiently regulating the molecular weight of COC by reversible coordination chain transfer, which achieves control of the molecular weight of COC by adding a metal alkyl compound as a chain transfer agent to the metallocene catalyst system, but causes the polymerization activity of the system to be significantly reduced and the molecular weight distribution to be widened.
[0007] Therefore, it is of great significance to study a catalytic system for preparing cycloolefin copolymers and apply the catalytic system to prepare cycloolefin copolymers to solve the problems existing in the prior art. Summary of the invention
[0008] The purpose of the present invention is to solve the problems existing in the prior art and provide a catalytic system for preparing cycloolefin copolymers and its application.
[0009] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0010] A catalytic system for preparing cycloolefin copolymers, comprising a main catalyst, a co-catalyst and a chain transfer agent;
[0011] The main catalyst is a silane-bridged fluorenylamino dimethyl titanium complex, a silane-bridged fluorenylamino dimethyl zirconium complex, a silane-bridged fluorenylamino dimethyl hafnium complex or a silane-bridged fluorenylamino dichloro hafnium complex;
[0012] The co-catalyst is an aluminum compound co-catalyst or a boron compound co-catalyst, belonging to the third main group complex;
[0013] The chain transfer agent is one or more of the second main / sub-group metal complexes;
[0014] The molar ratio of the aluminum compound co-catalyst to the main catalyst is 1 to 1000:1, preferably 200 to 800:1, and more preferably 400:1; the molar ratio of the boron compound co-catalyst to the main catalyst is 1 to 10:1, preferably 1 to 5:1, and more preferably 2:1; the molar ratio of the chain transfer agent to the main catalyst is 1 to 500:1, preferably 1 to 100:1, and more preferably 2 to 20:1.
[0015] The catalytic properties of the metallocene catalyst used for COC polymerization are closely related to the type of central metal, the structure of the ligand, the configuration and conformation of the complex. When cycloolefins and acyclic olefins are polymerized, the cycloolefins with larger monomer volume will produce steric hindrance, making it difficult to coordinate to the metallocene active center with a narrow space and insert active chains, resulting in low polymerization activity or even failure of polymerization of COC obtained by catalysis of many metallocene catalysts. The bridged single metallocene catalyst (silane-bridged fluorenylamino dimethyl titanium complex, silane-bridged fluorenylamino dimethyl zirconium complex, silane-bridged fluorenylamino dimethyl hafnium complex or silane-bridged fluorenylamino dichloro hafnium complex) used in the present invention has the typical characteristics of a semi-sandwich structure. The metallocene ligand covers one side of the metal center, while a large coordination space is left on the other side, which is conducive to the coordination and insertion polymerization of cycloolefin monomers. The polymerization activity is very high when COC is prepared without adding a chain transfer agent, and can reach up to 5×10 8 g·mol -1 ·h -1 At the same time, the bridged single metallocene catalyst catalyzes the polymerization of cycloolefins and non-cyclic olefins to form an active polymerization system. Without adding a chain transfer agent, the weight average molecular weight of COC increases with the increase of the cycloolefin monomer feed amount and the polymerization time, reaching a maximum of 60×10 4 g / mol (the molecular weight is too high to be processed) and the molecular weight distribution is narrow (molecular weight distribution ≤ 3).
[0016] The coordination polymerization mechanism of the metallocene catalytic system is the coordination of olefin molecules and transition metals, which is usually composed of four elementary reactions: chain initiation, chain growth, chain transfer, and chain termination. Chain transfer refers to the process of transferring the active chain from the active center to another molecule, which mainly includes β-H elimination and chain transfer to alkyl metals. The number of molecular chains of COC obtained by polymerization of the bridged single metallocene catalyst system used in the present invention is less than the amount of catalyst added, indicating that there is no chain transfer reaction caused by β-H elimination in the copolymerization process initiated by the system. After adding the chain transfer agent, the chain transfer reaction (including chain termination) in the system is mainly to the alkyl metal, and the chain transfer rate kt Much larger than the chain growth rate k p , the chain transfer reaction at this time is usually reversible and rapid, and the process is called coordination chain transfer polymerization (CCTP). In CCTP, the most important thing is the chain transfer agent, which is usually some metal alkyls such as alkyl aluminum, alkyl zinc, and alkyl magnesium. CCTP solves the shortcomings of metallocene catalysts, that is, most of the existing metallocene catalysts are active polymerization systems, and each active center can only generate one active chain. In CCTP, the active chain growing on the active center is transferred to the alkyl metal as a chain transfer agent to form a dormant species, while the active center continues to generate new active chains. Rapid and reversible chain transfer occurs between the growing active chain and the dormant species, and a dynamic balance is achieved between the active center, the alkyl metal and the active chain, so that each active center can generate multiple active chains with uniform chain lengths. Therefore, the obtained COC has a narrower molecular weight distribution. The molecular weight of the polymer can be controlled by changing the concentration of the chain transfer agent in the system. The higher the ratio of the chain transfer agent to the catalyst, the higher the transfer efficiency, and the more chains can be grown by each catalyst molecule, reducing the consumption of expensive metallocene catalysts. After adding the chain transfer agent, within a certain range, as the amount of chain transfer agent added increases, the polymerization activity of COC obtained by the bridged single metallocene catalyst system remains unchanged or even increases, and the molecular weight continues to decrease. As the amount of addition continues to increase, the activity decreases, but still remains at 1×10 7 g·mol -1 ·h -1 Above, the lowest weight average molecular weight can reach 1×10 3 The cycloolefin copolymer prepared by the present invention has the advantages of wide adjustable molecular weight range, narrow molecular weight distribution, controllable cycloolefin insertion rate and glass transition temperature, etc.
[0017] As the preferred technical solution:
[0018] The catalytic system for preparing cycloolefin copolymers as described above, wherein the main catalyst is methylphenylsilicon bridge group-(2,7-di-tert-butylfluorenyl)-(α-dimethylnaphthylamino)-dimethyltitanium, diphenylsilicon bridge group-(2,7-di-tert-butylfluorenyl)-(α-dimethylnaphthylamino)-dimethyltitanium, dimethylsilicon bridge group-fluorenyl-tert-butylamino-dimethyltitanium, dimethylsilicon bridge group-(2,7-di-tert-butylfluorenyl)-tert-butylamino-dimethyltitanium, dimethylsilicon bridge group-(3,6-di-tert-butylfluorenyl)-tert-butylamino-dimethyltitanium, dimethylsilicon bridge group-(3,6-dimethoxyfluorenyl)-tert-butylamino-dimethyltitanium, dimethylsilicon bridge group-(2,6-di(1,1,4,4-tetramethylcyclohexyl)fluorenyl)-tert-butylamino- Dimethyltitanium, dimethylsilyl bridge-fluorenyl-(α-dimethylanilino)-dimethyltitanium, dimethylsilyl bridge-(2,7-di-tert-butylfluorenyl)-(α-dimethylanilino)-dimethyltitanium, dimethylsilyl bridge-(3,6-di-tert-butylfluorenyl)-(α-dimethylanilino)-dimethyltitanium, dimethylsilyl bridge-(3,6-dimethoxyfluorenyl)-(α-dimethylanilino)-dimethyltitanium, dimethylsilyl bridge-(2,6-bis(1,1,4,4-tetramethylcyclohexyl)fluorenyl)-(α-dimethylanilino)-dimethyltitanium, dimethylsilyl bridge-fluorenyl-(α-dimethylnaphthylamino)-dimethyltitanium, dimethylsilyl bridge-(2,7-di-tert-butylfluorenyl)-(α-dimethylnaphthylamino)-dimethyl Titanium, dimethylsilyl bridge-(3,6-di-tert-butylfluorenyl)-(α-dimethylnaphthylamino)-dimethyl titanium, dimethylsilyl bridge-(3,6-dimethoxyfluorenyl)-(α-dimethylnaphthylamino)-dimethyl titanium, dimethylsilyl bridge-(2,6-bis(1,1,4,4-tetramethylcyclohexyl)fluorenyl)-(α-dimethylnaphthylamino)-dimethyl titanium, dimethylsilyl bridge-fluorenyl-adamantylamino-dimethyl titanium, dimethylsilyl bridge-(2,7-di-tert-butylfluorenyl)-adamantylamino-dimethyl titanium, dimethylsilyl bridge-(3,6-di-tert-butylfluorenyl)-adamantylamino-dimethyl titanium, dimethylsilyl bridge-(3,6-dimethoxyfluorenyl)-adamantylamino-dimethyl titanium, dimethylsilyl bridge-(2,6 -bis(1,1,4,4-tetramethylcyclohexyl)fluorenyl)-adamantanylamine-dimethyltitanium, dimethylsilyl bridge-fluorenyl-tert-butylamino-dimethylzirconium, dimethylsilyl bridge-(2,7-di-tert-butylfluorenyl)-tert-butylamino-dimethylzirconium, dimethylsilyl bridge-(3,6-di-tert-butylfluorenyl)-tert-butylamino-dimethylzirconium, dimethylsilyl bridge-(3,6-dimethoxyfluorenyl)-tert-butylamino-dimethylzirconium, dimethylsilyl bridge-(2,6-bis(1,1,4,4-tetramethylcyclohexyl)fluorenyl)-tert-butylamino-dimethylzirconium, dimethylsilyl bridge-fluorenyl-adamantanylamine-dimethylzirconium, dimethylsilyl bridge-(2,7-di-tert-butylfluorenyl)-adamantanylamine-dimethylzirconium, dimethylsilyl bridge-(3,6-di-tert-butylfluorenyl)-adamantylamine-dimethylzirconium, dimethylsilyl-(3,6-dimethoxyfluorenyl)-adamantylamine-dimethylzirconium, dimethylsilyl-(2,6-di(1,1,4,4-tetramethylcyclohexyl)fluorenyl)-adamantylamine-dimethylzirconium, dimethylsilyl-fluorenyl-tert-butylamino-dimethylhafnium, dimethylsilyl-fluorenyl-tert-butylamino-dimethylhafnium, dimethylsilyl-fluorenyl-tert-butylamino-dichlorohafnium or dimethylsilyl-fluorenyl-adamantylamine-dichlorohafnium.
[0019] The catalyst system for preparing cycloolefin copolymers as described above, wherein the aluminum compound co-catalyst is one or more of methylaluminoxane, modified methylaluminoxane, trialkylaluminum (trimethylaluminum, triethylaluminum, tripropylaluminum, triisopropylaluminum, tri-n-butylaluminum, triisobutylaluminum, tri-n-hexylaluminum, trioctylaluminum, tridecylaluminum), dialkylaluminum chloride (dimethylaluminum chloride, diethylaluminum chloride, n-propylaluminum monochloride, dibutylaluminum chloride, diisobutylaluminum chloride, di-n-hexylaluminum chloride), monoalkylaluminum dichloride (methylaluminum dichloride, ethylaluminum dichloride, isobutylaluminum dichloride, mono-n-hexylaluminum dichloride) and trialkylaluminum trichloride (trimethylaluminum trichloride, triethylaluminum trichloride), preferably methylaluminoxane or modified methylaluminoxane; the boron compound co-catalyst is N, N-dimethylanilinium tetrakis(pentafluorophenyl)borate, N , one or more of N-diethylanilinium tetrakis(pentafluorophenyl)borate, N,N-di(hexadecyl)anilinium tetrakis(pentafluorophenyl)borate, tris(pentafluorophenyl)borate, triphenylcarbonium tetrakis(pentafluorophenyl)borate and trityltetrakis(pentafluorophenyl)borate, preferably triphenylcarbonium tetrakis(pentafluorophenyl)borate.
[0020] In the catalyst system for preparing cycloolefin copolymers as described above, the chain transfer agent is one or more of diphenyl zinc, dimethyl zinc, diethyl zinc, diisopropyl zinc, dibutyl zinc, diethyl magnesium, diisobutyl magnesium, di-n-butyl magnesium and n-butylethyl magnesium.
[0021] The present invention also provides a method for preparing a cycloolefin copolymer, wherein the catalytic system as described above is used to copolymerize cycloolefins and non-cyclic olefins under the catalytic action thereof to prepare the cycloolefin copolymer.
[0022] As the preferred technical solution:
[0023] In the above-mentioned method for preparing a cycloolefin copolymer, the cycloolefin is an unsaturated cyclic olefin, and the structural formula is as follows:
[0024] ;
[0025] In the formula, m is 0, 1 or 2, and R2 and R3 are each independently selected from a hydrogen atom, an alkyl group and a cycloalkyl group;
[0026] The cycloolefin is preferably one or more of cyclopentadiene, dicyclopentadiene, norbornene, tetracyclododecene, and 1,4,5,8,9,10-trimethylene dodecahydroanthracene, and more preferably norbornene;
[0027] Acyclic olefins are C2~C20 straight-chain olefins with the following structural formula:
[0028] ;
[0029] In the formula, R1 is independently hydrogen or a saturated aliphatic hydrocarbon group having 1 to 19 carbon atoms;
[0030] The acyclic olefin is preferably one or more of ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene and 1-eicosene.
[0031] In the method for preparing the cycloolefin copolymer as described above, the reaction adopts a solution polymerization method and the copolymerization reaction is carried out in an organic solvent.
[0032] The organic solvent is one or more of aromatic hydrocarbons (toluene, ethylbenzene, xylene, trimethylbenzene), aliphatic hydrocarbons (n-pentane, isopentane, n-hexane, isohexane, n-heptane, isoheptane, n-octane, isooctane) and alicyclic hydrocarbons (cyclohexane, cycloheptane, cyclooctane, cyclohexanone, methylcyclohexane, methylcyclohexanone), preferably one or more of toluene, n-hexane, cyclohexane and methylcyclohexane, more preferably toluene.
[0033] In the method for preparing a cycloolefin copolymer as described above, the reaction temperature is 40-120°C, preferably 40-60°C, more preferably 40°C; the reaction time is 1-30 min, preferably 1-5 min, more preferably 3 min.
[0034] In the method for preparing a cyclic olefin copolymer as described above, the molar ratio of the cyclic olefin to the non-cyclic olefin is 1-10:1.
[0035] A method for preparing a cycloolefin copolymer as described in any one of the above items, wherein the weight average molecular weight of the cycloolefin copolymer is 1×10 3 ~60×10 4 g / mol, molecular weight distribution is 1.5~3.0, polymerization activity is 1×10 7 ~5×10 8 g mol -1The polymerization activity refers to the unit mass of the polymer obtained by catalyzing the polymerization using a unit mole of catalyst per unit time. The glass transition temperature is 67~147 ℃, and the cycloolefin insertion rate is 21.0~51.1 mol%; the reaction equation is as follows Figure 6 shown.
[0036] The present invention also provides a cycloolefin copolymer prepared by any of the preparation methods described above, the structural formula of which is as follows:
[0037] ;
[0038] Among them, 1≤X / Y≤5, 2≤n≤5000;
[0039] R1 is independently hydrogen or a saturated aliphatic hydrocarbon group having 1 to 19 carbon atoms;
[0040] R2 and R3 are each independently selected from a hydrogen atom, an alkyl group and a cycloalkyl group.
[0041] Beneficial effects:
[0042] (1) A catalytic system for preparing cycloolefin copolymers of the present invention, wherein the chain transfer agent is a second main / sub-group metal complex, can significantly increase the chain transfer rate in the coordination polymerization process after the chain transfer agent is added, and the chain transfer from the catalyst to the chain transfer agent allows each catalyst molecule to grow several polymer chains, significantly reducing the consumption of expensive silane-bridged metal complexes and controlling the molecular weight of the polymer.
[0043] (2) A method for preparing a cycloolefin copolymer of the present invention, wherein the obtained cycloolefin copolymer has the advantages of adjustable molecular weight in a wide range, narrow molecular weight distribution, controllable cycloolefin insertion rate and glass transition temperature, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 The main catalyst in Example 2 of the present invention 1 H NMR spectrum (CDCl3, 298K);
[0045] Figure 2 The cycloolefin copolymer prepared in Example 2 of the present invention is 13 C NMR spectrum (C2D2Cl4, 368K);
[0046] Figure 3 is a gel permeation chromatogram of the cyclic olefin copolymer prepared in Example 2 of the present invention;
[0047] Figure 4 is a DSC curve diagram of the cycloolefin copolymer prepared in Example 1 of the present invention;
[0048] Figure 5is a DSC curve diagram of the cycloolefin copolymer prepared in Example 2 of the present invention;
[0049] Figure 6 This is the reaction equation for preparing the cycloolefin copolymer by copolymerization of cycloolefin and non-cyclic olefin in the present invention. DETAILED DESCRIPTION
[0050] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0051] The test methods involved in the performance indicators in the embodiments and comparative examples of the present invention are as follows:
[0052] (1) Catalyst catalytic polymerization activity: The calculation formula is as follows:
[0053] ;
[0054] In the calculation formula, the catalyst catalytic polymerization activity (Activity) refers to the unit mass of COC obtained by catalytic polymerization using a unit mole of catalyst per unit time, and the unit is g·mol -1 ·h -1 .W 聚合物 : The mass of polymer catalyzed in a certain period of time (unit: g). [M]: The molar amount of catalyst in the experiment (unit: mol). t: The polymerization time (unit: h).
[0055] (2) Glass transition temperature: T of the COC product obtained in the experiment g The measurement was completed on a TA Q2000 differential scanning calorimeter (DSC), and the steps were as follows: weigh about 5 mg of COC sample, encapsulate it in an aluminum crucible and place it on the instrument test platform, and measure it in an inert atmosphere environment and a preset temperature program (heating and cooling rate: 10 ℃ / min; heating range: 40 ~250 ℃). First, the sample was kept at a constant temperature of 40 ℃ for 2 min, then heated from 40 ℃ to 250 ℃ at a heating rate of 10 ℃ / min to eliminate the thermal history, then cooled from 250 ℃ to 40 ℃ at the same cooling rate and kept at a constant temperature for 5 min again, and finally heated from 40 ℃ to 250 ℃ at a heating rate of 10 ℃ / min again, retaining the heat flow curve of the second heating, and calibrating its slope midline through a computer program to calculate T g .
[0056] (3) Weight average molecular weight and molecular weight distribution: The determination and characterization of polymer molecular weight and its distribution were completed on Agilent's PL GPC-220 high temperature gel chromatograph (equipped with PL# 1110-1120 guard column and 30 cm PLgel 10 μmM\IXED-B 7.5×300 mm column). About 20 mg of COC sample was weighed into a sample bottle and dissolved with 1,2,4-trichlorobenzene (TCB) solvent at 150 °C; after it was completely dissolved, a portion of the solution was transferred to the test bottle using a filter gun, and the test bottle was placed in the automatic sampler for testing. After setting the test parameters, the test was carried out. After the test was completed, the CIRRUS software was used for data analysis. The test conditions were: temperature: 150 °C; mobile phase: 1,2,4-trichlorobenzene (TCB); flow rate: 1.0 mol / L; calibration standard: narrow distribution polystyrene. If the M w As the horizontal axis, the curve obtained in this way is a curve that almost coincides with the X-axis, and the change in the amount of substance cannot be reflected on the curve. Therefore, log M is usually used w To replace M w Make a picture.
[0057] (4) Nuclear magnetic resonance spectra: The polymer chain structure was determined by Bruker Asend TM The results were obtained using a 600 MHz NMR spectrometer. 13 The integration results on the C NMR spectrum are used to calculate the cycloolefin insertion rate. About 100 mg of the purified COC sample is weighed and placed in a nuclear magnetic tube, and 1,1,2,2-deuterated tetrachloroethane is used as the solvent. The sample is then sealed in the nuclear magnetic tube and heated for 6 h. After it is completely dissolved, it is tested at 368 K under liquid nitrogen protection. Taking the cycloolefin copolymer obtained by copolymerization of ethylene (E) and norbornene (NB) as an example, the NB monomer insertion rate is calculated according to the following calculation formula:
[0058] ;
[0059] Among them, I C1 / 4 ,I C2 / 3 and I C7 The values correspond to the integrated areas of the C1 / 4, C2 / 3 and C7 characteristic peaks of NB, respectively. CH2 The value corresponds to the sum of the integrated areas of the C5 / C6 and ethylene CH2 characteristic peaks of NB;
[0060] .
[0061] The sources of some substances in the examples and comparative examples of the present invention are as follows:
[0062] Methylaluminoxane: Ron's reagent, R129768-100ml.
[0063] Triphenylcarbonium tetrakis(pentafluorophenyl)borate: Ron's reagent, R055487-200mg.
[0064] Modified methylaluminoxane: Ailan (Shanghai) Chemical Technology Co., Ltd., 206451-54-9.
[0065] N, N-Dimethylanilinium tetrakis(pentafluorophenyl)borate: Shanghai Haohong Biopharmaceutical Technology Co., Ltd., 1176862-250mg.
[0066] Diethylaluminum chloride: Shanghai Titan Co., Ltd., 01376488.
[0067] Ethyl aluminum dichloride: Shanghai Titan Co., Ltd., 01376488.
[0068] Ethyl aluminum dichloride: Shanghai Titan Co., Ltd., 011343043.
[0069] Trityltetrakis(pentafluorophenyl)borate: Shanghai BiDe Pharmaceutical Technology Co., Ltd., BD232925.
[0070] Diethylzinc: Shanghai Aladdin Biochemical Technology Co., Ltd., D107431-25mL.
[0071] Diphenylzinc: Shanghai MacLean Biochemical Technology Co., Ltd., D776224-100mg 5mL.
[0072] Dimethylzinc: Shanghai Aladdin Biochemical Technology Co., Ltd., D140708-100mL.
[0073] Di-n-butylmagnesium: Ron's reagent, R007478-100mL.
[0074] Dibutylzinc: Shanghai Aladdin Biochemical Technology Co., Ltd., D188990-100mL.
[0075] Diisopropylzinc: Shanghai Aladdin Biochemical Technology Co., Ltd., D466158-.
[0076] n-Butylethylmagnesium: Shanghai Aladdin Biochemical Technology Co., Ltd., B140756-5mL.
[0077] Toluene: Sinopharm Chemical Reagent Co., Ltd., 10022828.
[0078] Methylcyclohexane: Shanghai Titan Co., Ltd., 01006977.
[0079] n-Hexane: Sinopharm Chemical Reagent Co., Ltd., 80068618.
[0080] n-Heptane: Ron's reagent, R033323-500mL.
[0081] n-Pentane: Shanghai Aladdin Biochemical Technology Co., Ltd., P298686-2.5L.
[0082] Cycloheptane: Shanghai Titan Co., Ltd., 013556616.
[0083] Cyclohexane: Sinopharm Chemical Reagent Co., Ltd., 80039728.
[0084] n-Pentane: MACKLIN, P816220-500mL.
[0085] Xylene: Sinopharm Chemical Reagent Co., Ltd., 10023428.
[0086] Norbornene: Shanghai Myrel, M17722-100G.
[0087] Tetracyclododecene: Shanghai Titan Co., Ltd., 013629869.
[0088] Cyclopentadiene: MACKLIN, C875529-100g.
[0089] Dicyclopentadiene: Shanghai Titan Co., Ltd., 01115014.
[0090] Ethylene: Shanghai Qihui, YG0020.
[0091] 1-Butene: Shanghai Titan Co., Ltd., 016240820.
[0092] 1-Heptene: Shanghai Merrill, M20715-100 mL.
[0093] Propylene: Shanghai Qihui, YG0019.
[0094] 1-Hexene: Shanghai Titan Co., Ltd., 01092680
[0095] 1-Pentene: Shanghai Bailingwei Chemical Technology Co., Ltd., P0316.
[0096] 1-Octene: Shanghai J&K Chemical Technology Co., Ltd., 914719.
[0097] 1-Dodecene: Sane Chemical Technology (Shanghai) Co., Ltd., W3300890250.
[0098] Nitrogen: Shanghai Qihui, YG0003.
[0099] Argon: Shanghai Qihui, YG0008.
[0100] Helium: Shanghai Qihui, YG0001.
[0101] Methanol: Shanghai Titan Co., Ltd., 01273159.
[0102] Ethanol: Ron's reagent, R051411-500mL.
[0103] Isopropyl alcohol: Shanghai Merrill, M23307-500mL.
[0104] Acetone: Sinopharm Chemical Reagent Co., Ltd., 10000428.
[0105] Cyclohexanone: Shanghai Titan Co., Ltd., 01007022.
[0106] Example 1
[0107] A catalytic system for preparing cycloolefin copolymers, comprising a main catalyst, a co-catalyst and a chain transfer agent;
[0108] The main catalyst is dimethylsilyl bridge group-(2,7-di-tert-butylfluorenyl)-tert-butylamino-dimethyltitanium;
[0109] The co-catalyst is methylaluminoxane;
[0110] The chain transfer agent is diethyl zinc;
[0111] The molar ratio of the co-catalyst to the main catalyst is 400:1; the molar ratio of the chain transfer agent to the main catalyst is 20:1.
[0112] A method for preparing a cycloolefin copolymer, comprising the following steps:
[0113] (1) Preparation of raw materials:
[0114] Organic solvent: toluene;
[0115] Cyclic olefins: norbornene;
[0116] Acyclic olefins: propylene;
[0117] The above-mentioned catalytic system for preparing cycloolefin copolymers includes a main catalyst, a co-catalyst and a chain transfer agent;
[0118] Propylene gas at a pressure of 5 atm;
[0119] Methanol;
[0120] Acidified precipitant: The acid is hydrochloric acid, and the precipitant is methanol, Shanghai Titan Co., Ltd.;
[0121] (2) Under nitrogen protection, organic solvent, cycloolefin, chain transfer agent, and co-catalyst are added to the reaction vessel in sequence, acyclic olefin is introduced, and then the main catalyst is added, and copolymerization is carried out at 40 °C for 3 min. After the reaction is completed, methanol is added to terminate the polymerization;
[0122] The molar ratio of the organic solvent to the cyclic olefin is 16:1; the molar ratio of the cyclic olefin to the non-cyclic olefin is 5:1; the molar ratio of the cyclic olefin to the chain transfer agent is 67:1;
[0123] (3) pouring the reaction solution obtained from the polymerization reaction in step (2) into a container containing an acidified precipitant, and then filtering, washing with methanol three times, and vacuum drying in sequence to obtain a cycloolefin copolymer;
[0124] The vacuum degree of vacuum drying is 0.01 atm, the temperature is 60 °C, and the time is 12 hours.
[0125] The weight average molecular weight of the cycloolefin copolymer finally obtained was 1.6×10 3 g / mol, molecular weight distribution is 1.7, and polymerization activity is 4.7×10 8 g mol -1 , the cycloolefin insertion rate is 50.80 mol%; Figure 4 As shown, the glass transition temperature is 145 °C.
[0126] Comparative Example 1
[0127] A catalytic system for preparing cycloolefin copolymers is basically the same as Example 1, except that no chain transfer agent is added.
[0128] A method for preparing a cycloolefin copolymer adopts the above catalyst system for catalysis.
[0129] The weight average molecular weight of the cycloolefin copolymer finally obtained is 58×10 4 g / mol, molecular weight distribution is 1.5, and polymerization activity is 4.8×10 8 g mol -1 h -1 .
[0130] By comparing Comparative Example 1 with Example 1, it can be found that the weight average molecular weight of the cycloolefin copolymer obtained in Comparative Example 1 is significantly higher than that in Example 1. This is because the polymerization of cycloolefins and non-cyclic olefins catalyzed by the catalyst is "living polymerization", and it is difficult for chain transfer reactions to occur in the system. Each active center can only generate one active chain and continue to grow, so the molecular weight of the cycloolefin copolymer finally obtained is very high.
[0131] Comparative Example 2
[0132] A catalytic system for preparing cycloolefin copolymers is basically the same as that in Example 1, except that the co-catalyst is sodium tetrakis(pentafluorophenyl)borate.
[0133] A method for preparing a cycloolefin copolymer adopts the above catalyst system for catalysis.
[0134] The weight average molecular weight of the cycloolefin copolymer finally obtained was 2.1×10 3 g / mol, molecular weight distribution is 1.8, polymerization activity is 6.0×10 6 g mol -1 h -1 .
[0135] Comparing Comparative Example 2 with Example 1, it can be found that the polymerization activity of the cycloolefin copolymer obtained in Comparative Example 2 is significantly lower than that in Example 1. This is because although sodium tetrakis(pentafluorophenyl)borate can induce the metallocene complex to form an active center, the stability of the active center is poor, causing a part of the active center to be directly deactivated, so the polymerization activity is greatly reduced.
[0136] Comparative Example 3
[0137] A catalytic system for preparing cycloolefin copolymers is basically the same as Example 1, except that the chain transfer agent is phenylsilane.
[0138] A method for preparing a cycloolefin copolymer adopts the above catalyst system for catalysis.
[0139] The weight average molecular weight of the cycloolefin copolymer finally obtained was 69.1×10 4 g / mol, molecular weight distribution is 2.1, and polymerization activity is 4.2×10 8 g mol -1 h -1 .
[0140] By comparing Comparative Example 3 with Example 1, it can be found that the weight average molecular weight of the cycloolefin copolymer obtained in Comparative Example 3 is significantly higher than that in Example 1. This is because there is an irreversible chain transfer reaction between the growing active chains and the dormant species. The growing active chains on the active centers are directly terminated by transferring to the chain transfer agent, and the active centers continue to generate new active chains.
[0141] Comparative Example 4
[0142] A catalytic system for preparing cycloolefin copolymers is basically the same as Example 1, except that the molar ratio of the aluminum complex co-catalyst to the main catalyst is 1050:1.
[0143] A method for preparing a cycloolefin copolymer adopts the above catalyst system for catalysis.
[0144] The weight average molecular weight of the cycloolefin copolymer finally obtained was 1.9×10 3 g / mol, molecular weight distribution is 1.6, and polymerization activity is 1.4×10 6 g mol -1 h -1 .
[0145] By comparing Comparative Example 4 with Example 1, it can be found that the polymerization activity of the cycloolefin copolymer obtained in Comparative Example 4 is significantly lower than that in Example 1. This is because there are unreacted raw materials in the process of synthesizing the aluminum compound co-catalyst. As the amount of the aluminum compound co-catalyst added increases, the raw materials are more easily complexed with the main catalyst to form a double coordination product, making it impossible for the metallocene complex after the alkyl to produce vacancies, reducing the active species formed by the metallocene complex, and reducing the polymerization activity.
[0146] Comparative Example 5
[0147] A catalytic system for preparing cycloolefin copolymers is basically the same as Example 1, except that the ratio of chain transfer agent to main catalyst is 510:1.
[0148] A method for preparing a cycloolefin copolymer adopts the above catalyst system for catalysis.
[0149] The weight average molecular weight of the cycloolefin copolymer finally obtained is 2.8×10 3 g / mol, molecular weight distribution is 1.8, polymerization activity is 8.9×10 6 g mol -1 h -1 .
[0150] By comparing Comparative Example 5 with Example 1, it can be found that the polymerization activity of the cycloolefin copolymer obtained in Comparative Example 5 is significantly lower than that in Example 1. This is because as the amount of chain transfer agent added increases, the concentration of the chain transfer agent in the system increases, and the probability of chain transfer increases accordingly. The active chain growing on the active center is transferred to the chain transfer agent before sufficient chain growth has been carried out, thereby reducing the polymerization activity.
[0151] Example 2
[0152] A catalytic system for preparing cycloolefin copolymers, comprising a main catalyst, a co-catalyst and a chain transfer agent;
[0153] like Figure 1 As shown, the main catalyst is dimethylsilyl bridge group-fluorenyl-tert-butylamino-dimethyltitanium;
[0154] The co-catalyst is triphenylcarbonium tetrakis(pentafluorophenyl)borate;
[0155] The chain transfer agent is diethyl zinc;
[0156] The molar ratio of the co-catalyst to the main catalyst is 2:1; the molar ratio of the chain transfer agent to the main catalyst is 10:1.
[0157] A method for preparing a cycloolefin copolymer, comprising the following steps:
[0158] (1) Preparation of raw materials:
[0159] Organic solvent: toluene;
[0160] Cyclic olefins: norbornene;
[0161] Acyclic olefins: ethylene;
[0162] The above-mentioned catalytic system for preparing cycloolefin copolymers includes a main catalyst, a co-catalyst and a chain transfer agent;
[0163] Ethylene gas at a pressure of 5 atm;
[0164] Methanol;
[0165] Acidified precipitant: The acid is hydrochloric acid and the precipitant is ethanol;
[0166] (2) Under nitrogen protection, organic solvent, cycloolefin, chain transfer agent, and co-catalyst are added to the reaction vessel in sequence, acyclic olefin is introduced, and then the main catalyst is added, and copolymerization is carried out at 40 °C for 3 min. After the reaction is completed, methanol is added to terminate the polymerization;
[0167] The molar ratio of the organic solvent to the cyclic olefin is 16:1; the molar ratio of the cyclic olefin to the non-cyclic olefin is 5:1; the molar ratio of the cyclic olefin to the chain transfer agent is 135:1;
[0168] (3) pouring the reaction solution obtained from the polymerization reaction in step (2) into a container containing an acidified precipitant, and then filtering, washing with ethanol three times, and vacuum drying in sequence to obtain a cycloolefin copolymer;
[0169] The vacuum degree of vacuum drying is 0.05 atm, the temperature is 65 °C, and the time is 9 hours.
[0170] like Figure 3 As shown in FIG. 1 , the weight average molecular weight of the cycloolefin copolymer finally obtained is 1.0×10 3 g / mol, molecular weight distribution is 1.5, polymerization activity is 5.0×10 8 g mol -1 ,like Figure 2 As shown, the cycloolefin insertion rate is 51.10 mol%; Figure 5 As shown, the glass transition temperature is 147 °C.
[0171] Comparative Example 6
[0172] A catalytic system for preparing cycloolefin copolymers is basically the same as Example 2, except that the molar ratio of the co-catalyst to the main catalyst is 11:1.
[0173] A method for preparing a cycloolefin copolymer adopts the above catalyst system for catalysis.
[0174] The weight average molecular weight of the cycloolefin copolymer finally obtained was 71.3×10 4 g / mol, molecular weight distribution is 1.5, and polymerization activity is 4.7×10 8 g mol -1 h -1 .
[0175] By comparing Comparative Example 6 with Example 2, it can be found that the weight average molecular weight of the cycloolefin copolymer obtained in Comparative Example 6 is significantly higher than that in Example 2. This is because the amount of co-catalyst added is increased, the concentration of the boron compound in the system is higher, it is easier to form an active center with the metallocene, occupy the vacant position on the metallocene complex for a long time, and slow down the transfer of the active chain to the chain transfer agent.
[0176] Comparative Example 7
[0177] A catalytic system for preparing cycloolefin copolymers is basically the same as Example 2, except that no chain transfer agent is added.
[0178] A method for preparing a cycloolefin copolymer adopts the above catalyst system for catalysis.
[0179] The weight average molecular weight of the cycloolefin copolymer finally obtained is 60×10 4 g / mol, molecular weight distribution is 1.6, and polymerization activity is 4.9×10 8 g mol -1 h -1 .
[0180] By comparing Comparative Example 7 with Example 2, it can be found that the weight average molecular weight of the cycloolefin copolymer obtained in Comparative Example 7 is significantly greater than that in Example 2. This is because the catalyst catalyzes the polymerization of cycloolefins and non-cyclic olefins in an "active polymerization" manner, and chain transfer reactions are difficult to occur in the system. Each active center can only generate one active chain and continue to grow, so the molecular weight of the cycloolefin copolymer finally obtained is very high.
[0181] Example 3
[0182] A catalytic system for preparing cycloolefin copolymers, comprising a main catalyst, a co-catalyst and a chain transfer agent;
[0183] The main catalyst is dimethylsilyl bridge group-(3,6-di-tert-butylfluorenyl)-(α-dimethylanilino)-dimethyltitanium;
[0184] The co-catalyst is modified methylaluminoxane;
[0185] The chain transfer agent is dimethyl zinc;
[0186] The molar ratio of the co-catalyst to the main catalyst is 200:1; the molar ratio of the chain transfer agent to the main catalyst is 40:1.
[0187] A method for preparing a cycloolefin copolymer, comprising the following steps:
[0188] (1) Preparation of raw materials:
[0189] Organic solvent: cyclohexane;
[0190] Cyclic olefins: tetracyclododecene;
[0191] Acyclic olefins: propylene;
[0192] The above-mentioned catalytic system for preparing cycloolefin copolymers includes a main catalyst, a co-catalyst and a chain transfer agent;
[0193] Propylene gas at a pressure of 3 atm;
[0194] Methanol;
[0195] Acidified precipitant: The acid is hydrochloric acid and the precipitant is methanol;
[0196] (2) Under the protection of helium, an organic solvent, a cyclic olefin, a chain transfer agent, and a co-catalyst are sequentially added to the reaction vessel, and then a non-cyclic olefin is introduced, and then a main catalyst is added, and then a copolymerization reaction is carried out at 50 °C for 1 min. After the reaction is completed, methanol is added to terminate the polymerization;
[0197] The molar ratio of the organic solvent to the cyclic olefin is 13:1; the molar ratio of the cyclic olefin to the non-cyclic olefin is 7:1; the molar ratio of the cyclic olefin to the chain transfer agent is 74:1;
[0198] (3) pouring the reaction solution obtained from the polymerization reaction in step (2) into a container containing an acidified precipitant, and then filtering, washing with ethanol three times, and vacuum drying in sequence to obtain a cycloolefin copolymer;
[0199] The vacuum degree of vacuum drying is 0.02 atm, the temperature is 65 °C, and the time is 8 hours.
[0200] The weight average molecular weight of the cycloolefin copolymer finally obtained was 5.4×10 3 g / mol, molecular weight distribution is 1.8, polymerization activity is 1.2×10 8 g mol -1 , the glass transition temperature is 121 ℃, and the cycloolefin insertion rate is 42.10 mol%.
[0201] Example 4
[0202] A catalytic system for preparing cycloolefin copolymers, comprising a main catalyst, a co-catalyst and a chain transfer agent;
[0203] The main catalyst is dimethylsilyl bridge group-(2,7-di-tert-butylfluorenyl)-adamantylamine-dimethyltitanium;
[0204] The co-catalyst is triphenylcarbonium tetrakis(pentafluorophenyl)borate;
[0205] The chain transfer agent is dibutyl zinc;
[0206] The molar ratio of the co-catalyst to the main catalyst is 1:1; the molar ratio of the chain transfer agent to the main catalyst is 80:1.
[0207] A method for preparing a cycloolefin copolymer, comprising the following steps:
[0208] (1) Preparation of raw materials:
[0209] Organic solvent: n-hexane;
[0210] Cyclic olefins: norbornene;
[0211] Acyclic olefins: ethylene;
[0212] The above-mentioned catalytic system for preparing cycloolefin copolymers includes a main catalyst, a co-catalyst and a chain transfer agent;
[0213] Ethylene gas at a pressure of 3 atm;
[0214] Methanol;
[0215] Acidified precipitant: The acid is hydrochloric acid and the precipitant is ethanol;
[0216] (2) Under argon protection, organic solvent, cycloolefin, chain transfer agent, and co-catalyst are added to the reaction vessel in sequence, acyclic olefin is introduced, and then the main catalyst is added, and copolymerization is carried out at 50 °C for 5 min. After the reaction is completed, methanol is added to terminate the polymerization;
[0217] The molar ratio of the organic solvent to the cyclic olefin is 21:1; the molar ratio of the cyclic olefin to the non-cyclic olefin is 10:1; the molar ratio of the cyclic olefin to the chain transfer agent is 104:1;
[0218] (3) pouring the reaction solution obtained from the polymerization reaction in step (2) into a container containing an acidified precipitant, followed by filtering, washing with isopropanol four times, and vacuum drying to obtain a cycloolefin copolymer;
[0219] The vacuum degree of vacuum drying is 0.04 atm, the temperature is 70 °C, and the time is 7 hours.
[0220] The weight average molecular weight of the cycloolefin copolymer finally obtained was 7.1×10 3 g / mol, molecular weight distribution is 2.0, and polymerization activity is 2.1×10 8 g mol -1 , the glass transition temperature is 128 ℃, and the cycloolefin insertion rate is 43.40 mol%.
[0221] Example 5
[0222] A catalytic system for preparing cycloolefin copolymers, comprising a main catalyst, a co-catalyst and a chain transfer agent;
[0223] The main catalyst is dimethylsilyl bridge group-(3,6-dimethoxyfluorenyl)-adamantylamine-dimethyltitanium;
[0224] The co-catalyst is modified methylaluminoxane;
[0225] The chain transfer agent is diphenyl zinc;
[0226] The molar ratio of the co-catalyst to the main catalyst is 800:1; the molar ratio of the chain transfer agent to the main catalyst is 100:1.
[0227] A method for preparing a cycloolefin copolymer, comprising the following steps:
[0228] (1) Preparation of raw materials:
[0229] Organic solvent: methylcyclohexane;
[0230] Cyclic olefins: tetracyclododecene;
[0231] Acyclic olefins: ethylene;
[0232] The above-mentioned catalytic system for preparing cycloolefin copolymers includes a main catalyst, a co-catalyst and a chain transfer agent;
[0233] Ethylene gas at a pressure of 3 atm;
[0234] Methanol;
[0235] Acidified precipitant: The acid is hydrochloric acid and the precipitant is isopropanol;
[0236] (2) Under argon protection, organic solvent, cycloolefin, chain transfer agent, and co-catalyst are added to the reaction vessel in sequence, acyclic olefin is introduced, and then the main catalyst is added, and copolymerization is carried out at 60 °C for 5 min. After the reaction is completed, methanol is added to terminate the polymerization;
[0237] The molar ratio of the organic solvent to the cyclic olefin is 100:1; the molar ratio of the cyclic olefin to the non-cyclic olefin is 1:1; the molar ratio of the cyclic olefin to the chain transfer agent is 2.7:1;
[0238] (3) pouring the reaction solution obtained from the polymerization reaction in step (2) into a container containing an acidified precipitant, followed by filtering, washing with isopropanol five times, and vacuum drying to obtain a cycloolefin copolymer;
[0239] The vacuum degree of vacuum drying is 0.1 atm, the temperature is 70 °C, and the time is 6 hours.
[0240] The weight average molecular weight of the cycloolefin copolymer finally obtained was 7.7×10 3 g / mol, molecular weight distribution is 2.1, and polymerization activity is 1.8×10 8 g mol -1 , the glass transition temperature is 113 ℃, and the cycloolefin insertion rate is 40.40 mol%.
[0241] Example 6
[0242] A catalytic system for preparing cycloolefin copolymers, comprising a main catalyst, a co-catalyst and a chain transfer agent;
[0243] The main catalyst is dimethylsilyl bridge group-(3,6-dimethoxyfluorenyl)-(α-dimethylnaphthylamino)-dimethyltitanium;
[0244] The co-catalyst is N, N-dimethylanilinium tetrakis(pentafluorophenyl)borate;
[0245] The chain transfer agent is dimethyl zinc;
[0246] The molar ratio of the co-catalyst to the main catalyst is 4:1; the molar ratio of the chain transfer agent to the main catalyst is 1:1.
[0247] A method for preparing a cycloolefin copolymer, comprising the following steps:
[0248] (1) Preparation of raw materials:
[0249] Organic solvent: n-hexane;
[0250] Cyclic olefins: tetracyclododecene;
[0251] Acyclic olefins: propylene;
[0252] The above-mentioned catalytic system for preparing cycloolefin copolymers includes a main catalyst, a co-catalyst and a chain transfer agent;
[0253] Propylene gas at a pressure of 3 atm;
[0254] Methanol;
[0255] Acidified precipitant: The acid is hydrochloric acid and the precipitant is acetone;
[0256] (2) Under nitrogen protection, organic solvent, cycloolefin, chain transfer agent, and co-catalyst were added to the reaction vessel in sequence, acyclic olefin was introduced, and then the main catalyst was added. The copolymerization reaction was then carried out at 60 °C for 1 min. After the reaction was completed, methanol was added to terminate the polymerization.
[0257] The molar ratio of the organic solvent to the cyclic olefin is 1:1; the molar ratio of the cyclic olefin to the non-cyclic olefin is 10:1; the molar ratio of the cyclic olefin to the chain transfer agent is 54:1;
[0258] (3) pouring the reaction solution obtained from the polymerization reaction in step (2) into a container containing an acidified precipitant, and then filtering, washing with acetone once, and vacuum drying in sequence to obtain a cycloolefin copolymer;
[0259] The vacuum degree of vacuum drying is 0.02 atm, the temperature is 62 °C, and the time is 11 hours.
[0260] The weight average molecular weight of the cycloolefin copolymer finally obtained was 8.2×10 3 g / mol, molecular weight distribution is 1.9, and polymerization activity is 9.6×10 7 g mol -1 , the glass transition temperature is 123 ℃, and the cycloolefin insertion rate is 42.70 mol%.
[0261] Example 7
[0262] A catalytic system for preparing cycloolefin copolymers, comprising a main catalyst, a co-catalyst and a chain transfer agent;
[0263] The main catalyst is diphenylsilyl bridge group-(2,7-di-tert-butylfluorenyl)-(α-dimethylnaphthylamino)-dimethyltitanium;
[0264] The co-catalyst is modified methylaluminoxane;
[0265] The chain transfer agent is di-n-butyl magnesium;
[0266] The molar ratio of the co-catalyst to the main catalyst is 1000:1; the molar ratio of the chain transfer agent to the main catalyst is 500:1.
[0267] A method for preparing a cycloolefin copolymer, comprising the following steps:
[0268] (1) Preparation of raw materials:
[0269] Organic solvent: n-heptane;
[0270] Cyclic olefins: norbornene;
[0271] Acyclic olefins: 1-hexene;
[0272] The above-mentioned catalytic system for preparing cycloolefin copolymers includes a main catalyst, a co-catalyst and a chain transfer agent;
[0273] The pressure is 1 atm;
[0274] Methanol;
[0275] Acidified precipitant: The acid is hydrochloric acid and the precipitant is methanol;
[0276] (2) Under nitrogen protection, an organic solvent, a cyclic olefin, a non-cyclic olefin, a chain transfer agent, a co-catalyst, and then a main catalyst are added to the reaction vessel in sequence, and then a copolymerization reaction is carried out at 120 °C for 30 min. After the reaction is completed, methanol is added to terminate the polymerization;
[0277] The molar ratio of the organic solvent to the cyclic olefin is 11:1; the molar ratio of the cyclic olefin to the non-cyclic olefin is 7:1; the molar ratio of the cyclic olefin to the chain transfer agent is 108:1;
[0278] (3) pouring the reaction solution obtained from the polymerization reaction in step (2) into a container containing an acidified precipitant, followed by filtering, washing with cyclohexanone twice, and vacuum drying to obtain a cycloolefin copolymer;
[0279] The vacuum degree of vacuum drying is 0.04 atm, the temperature is 64 °C, and the time is 10 hours.
[0280] The weight average molecular weight of the cycloolefin copolymer finally obtained is 2.5×10 4 g / mol, molecular weight distribution is 3.0, and polymerization activity is 2.6×10 7 g mol -1 , the glass transition temperature is 84 ℃, and the cycloolefin insertion rate is 33.80 mol%.
[0281] Example 8
[0282] A catalytic system for preparing cycloolefin copolymers, comprising a main catalyst, a co-catalyst and a chain transfer agent;
[0283] The main catalyst is dimethylsilyl bridge group-fluorenyl-tert-butylamino-dimethyl zirconium;
[0284] The co-catalyst is trityl tetrakis(pentafluorophenyl)borate;
[0285] The chain transfer agent is dibutyl zinc;
[0286] The molar ratio of the co-catalyst to the main catalyst is 10:1; the molar ratio of the chain transfer agent to the main catalyst is 200:1.
[0287] A method for preparing a cycloolefin copolymer, comprising the following steps:
[0288] (1) Preparation of raw materials:
[0289] Organic solvent: cyclohexane;
[0290] Cyclic olefins: norbornene;
[0291] Acyclic olefins: 1-octene;
[0292] The above-mentioned catalytic system for preparing cycloolefin copolymers includes a main catalyst, a co-catalyst and a chain transfer agent;
[0293] The pressure is 1 atm;
[0294] Methanol;
[0295] Acidified precipitant: The acid is hydrochloric acid and the precipitant is ethanol;
[0296] (2) Under argon protection, an organic solvent, a cyclic olefin, a non-cyclic olefin, a chain transfer agent, a co-catalyst, and then a main catalyst are added to the reaction vessel in sequence, and then a copolymerization reaction is carried out at 80 °C for 15 min. After the reaction is completed, methanol is added to terminate the polymerization;
[0297] The molar ratio of the organic solvent to the cyclic olefin is 23:1; the molar ratio of the cyclic olefin to the non-cyclic olefin is 4:1; the molar ratio of the cyclic olefin to the chain transfer agent is 95:1;
[0298] (3) pouring the reaction solution obtained from the polymerization reaction in step (2) into a container containing an acidified precipitant, and then filtering, washing with ethanol three times, and vacuum drying in sequence to obtain a cycloolefin copolymer;
[0299] The vacuum degree of vacuum drying is 0.06 atm, the temperature is 66 °C, and the time is 8 hours.
[0300] The weight average molecular weight of the cycloolefin copolymer finally obtained is 6×10 4 g / mol, molecular weight distribution is 2.6, and polymerization activity is 3.8×10 7 g mol -1 , the glass transition temperature is 78 ℃, and the cycloolefin insertion rate is 31.30 mol%.
[0301] Example 9
[0302] A catalytic system for preparing cycloolefin copolymers, comprising a main catalyst, a co-catalyst and a chain transfer agent;
[0303] The main catalyst is dimethylsilyl bridge group-(2,7-di-tert-butylfluorenyl)-adamantylamine-dimethylzirconium;
[0304] The co-catalyst is ethylaluminum dichloride;
[0305] The chain transfer agent is diisopropyl zinc;
[0306] The molar ratio of the co-catalyst to the main catalyst is 1:1; the molar ratio of the chain transfer agent to the main catalyst is 300:1.
[0307] A method for preparing a cycloolefin copolymer, comprising the following steps:
[0308] (1) Preparation of raw materials:
[0309] Organic solvent: n-pentane;
[0310] Cycloolefins: cyclopentadiene;
[0311] Acyclic olefins: 1-pentene;
[0312] The above-mentioned catalytic system for preparing cycloolefin copolymers includes a main catalyst, a co-catalyst and a chain transfer agent;
[0313] The pressure is 1 atm;
[0314] Methanol;
[0315] Acidified precipitant: The acid is hydrochloric acid and the precipitant is isopropanol;
[0316] (2) Under the protection of helium, an organic solvent, a cyclic olefin, a non-cyclic olefin, a chain transfer agent, a co-catalyst, and then a main catalyst are added to the reaction vessel in sequence, and then a copolymerization reaction is carried out at 90 °C for 30 min. After the reaction is completed, methanol is added to terminate the polymerization;
[0317] The molar ratio of the organic solvent to the cyclic olefin is 46:1; the molar ratio of the cyclic olefin to the non-cyclic olefin is 2:1; the molar ratio of the cyclic olefin to the chain transfer agent is 5.4:1;
[0318] (3) pouring the reaction solution obtained from the polymerization reaction in step (2) into a container containing an acidified precipitant, followed by filtering, washing with isopropanol four times, and vacuum drying to obtain a cycloolefin copolymer;
[0319] The vacuum degree of vacuum drying is 0.08 atm, the temperature is 68 °C, and the time is 7 hours.
[0320] The weight average molecular weight of the cycloolefin copolymer finally obtained was 4.7×10 4 g / mol, molecular weight distribution is 2.5, polymerization activity is 1.0×10 7 g mol -1 , the glass transition temperature is 67 ℃, and the cycloolefin insertion rate is 21.00 mol%.
[0321] Example 10
[0322] A catalytic system for preparing cycloolefin copolymers, comprising a main catalyst, a co-catalyst and a chain transfer agent;
[0323] The main catalyst is dimethylsilyl bridge group-fluorenyl-tert-butylamino-dimethylhafnium;
[0324] The co-catalyst is trityl tetrakis(pentafluorophenyl)borate;
[0325] The chain transfer agent is n-butyl ethyl magnesium;
[0326] The molar ratio of the co-catalyst to the main catalyst is 1:1; the molar ratio of the chain transfer agent to the main catalyst is 400:1.
[0327] A method for preparing a cycloolefin copolymer, comprising the following steps:
[0328] (1) Preparation of raw materials:
[0329] Organic solvent: xylene;
[0330] Cyclic olefins: dicyclopentadiene;
[0331] Acyclic olefins: 1-dodecene;
[0332] The above-mentioned catalytic system for preparing cycloolefin copolymers includes a main catalyst, a co-catalyst and a chain transfer agent;
[0333] The pressure is 1 atm;
[0334] Methanol;
[0335] Acidified precipitant: The acid is hydrochloric acid and the precipitant is acetone;
[0336] (2) Under nitrogen protection, an organic solvent, a cyclic olefin, a non-cyclic olefin, a chain transfer agent, a co-catalyst, and then a main catalyst are added to the reaction vessel in sequence, and then a copolymerization reaction is carried out at 100 °C for 20 min. After the reaction is completed, methanol is added to terminate the polymerization;
[0337] The molar ratio of the organic solvent to the cyclic olefin is 1:1; the molar ratio of the cyclic olefin to the non-cyclic olefin is 10:1; the molar ratio of the cyclic olefin to the chain transfer agent is 27:1;
[0338] (3) pouring the reaction solution obtained from the polymerization reaction in step (2) into a container containing an acidified precipitant, followed by filtering, washing with acetone five times and vacuum drying to obtain a cycloolefin copolymer;
[0339] The vacuum degree of vacuum drying is 0.09 atm, the temperature is 70 °C, and the time is 6 hours.
[0340] The weight average molecular weight of the cycloolefin copolymer finally obtained was 8.6×10 4 g / mol, molecular weight distribution is 3.0, and polymerization activity is 4.2×10 7 g mol -1 , the glass transition temperature is 74 ℃, and the cycloolefin insertion rate is 30.20 mol%.
[0341] Embodiment 11
[0342] A catalytic system for preparing cycloolefin copolymers, comprising a main catalyst, a co-catalyst and a chain transfer agent;
[0343] The main catalyst is dimethylsilyl bridge group-(2,7-di-tert-butylfluorenyl)-tert-butylamino-dimethylzirconium;
[0344] The co-catalyst is N, N-dimethylanilinium tetrakis(pentafluorophenyl)borate;
[0345] The chain transfer agent is di-n-butyl magnesium;
[0346] The molar ratio of the co-catalyst to the main catalyst is 900:1; the molar ratio of the chain transfer agent to the main catalyst is 500:1.
[0347] A method for preparing a cycloolefin copolymer, comprising the following steps:
[0348] (1) Preparation of raw materials:
[0349] Organic solvent: methylcyclohexane;
[0350] Cycloolefins: cyclopentadiene;
[0351] Acyclic olefins: 1-hexene;
[0352] The above-mentioned catalytic system for preparing cycloolefin copolymers includes a main catalyst, a co-catalyst and a chain transfer agent;
[0353] The pressure is 1 atm;
[0354] Methanol;
[0355] Acidified precipitant: The acid is hydrochloric acid and the precipitant is acetone;
[0356] (2) Under the protection of helium, an organic solvent, a cyclic olefin, a non-cyclic olefin, a chain transfer agent, a co-catalyst, and then a main catalyst are added to the reaction vessel in sequence, and then a copolymerization reaction is carried out at 70 °C for 10 min. After the reaction is completed, methanol is added to terminate the polymerization;
[0357] The molar ratio of the organic solvent to the cyclic olefin is 46:1; the molar ratio of the cyclic olefin to the non-cyclic olefin is 7:1; the molar ratio of the cyclic olefin to the chain transfer agent is 46:1;
[0358] (3) pouring the reaction solution obtained from the polymerization reaction in step (2) into a container containing an acidified precipitant, and then filtering, washing with isopropanol twice, and vacuum drying in sequence to obtain a cycloolefin copolymer;
[0359] The vacuum degree of vacuum drying is 0.01 atm, the temperature is 70 °C, and the time is 7 hours.
[0360] The weight average molecular weight of the cycloolefin copolymer finally obtained was 1.7×10 4 g / mol, molecular weight distribution is 2.4, and polymerization activity is 5.3×10 7 g mol -1 , the glass transition temperature is 77 ℃, and the cycloolefin insertion rate is 31.20 mol%.
[0361] Example 12
[0362] A catalytic system for preparing cycloolefin copolymers, comprising a main catalyst, a co-catalyst and a chain transfer agent;
[0363] The main catalyst is dimethylsilyl bridge group-fluorenyl-tert-butylamino-hafnium dichloride;
[0364] The co-catalyst is ethylaluminum dichloride;
[0365] The chain transfer agent is diphenyl zinc;
[0366] The molar ratio of the co-catalyst to the main catalyst is 8:1; the molar ratio of the chain transfer agent to the main catalyst is 200:1.
[0367] A method for preparing a cycloolefin copolymer, comprising the following steps:
[0368] (1) Preparation of raw materials:
[0369] Organic solvent: n-heptane;
[0370] Cyclic olefins: dicyclopentadiene;
[0371] Acyclic olefins: 1-octene;
[0372] The above-mentioned catalytic system for preparing cycloolefin copolymers includes a main catalyst, a co-catalyst and a chain transfer agent;
[0373] The pressure is 1 atm;
[0374] Methanol;
[0375] Acidified precipitant: The acid is hydrochloric acid and the precipitant is isopropanol;
[0376] (2) Under nitrogen protection, an organic solvent, a cyclic olefin, a non-cyclic olefin, a chain transfer agent, a co-catalyst, and then a main catalyst are added to the reaction vessel in sequence, and then a copolymerization reaction is carried out at 110 °C for 10 min. After the reaction is completed, methanol is added to terminate the polymerization;
[0377] The molar ratio of the organic solvent to the cyclic olefin is 58:1; the molar ratio of the cyclic olefin to the non-cyclic olefin is 6:1; the molar ratio of the cyclic olefin to the chain transfer agent is 68:1;
[0378] (3) pouring the reaction solution obtained from the polymerization reaction in step (2) into a container containing an acidified precipitant, and then filtering, washing once with isopropanol, and vacuum drying in sequence to obtain a cycloolefin copolymer;
[0379] The vacuum degree of vacuum drying is 0.1 atm, the temperature is 60 °C, and the time is 6 hours.
[0380] The weight average molecular weight of the cycloolefin copolymer finally obtained is 2.3×10 4 g / mol, molecular weight distribution is 2.2, and polymerization activity is 1.6×10 7 g mol -1 , the glass transition temperature is 81 ℃, and the cycloolefin insertion rate is 33.40 mol%.
[0381] Embodiment 13
[0382] A catalytic system for preparing cycloolefin copolymers, comprising a main catalyst, a co-catalyst and a chain transfer agent;
[0383] The main catalyst is dimethylsilyl bridge group-(3,6-di-tert-butylfluorenyl)-tert-butylamino-dimethyltitanium;
[0384] The co-catalyst is diethylaluminum chloride;
[0385] The chain transfer agent is dibutyl zinc;
[0386] The molar ratio of the co-catalyst to the main catalyst is 200:1; the molar ratio of the chain transfer agent to the main catalyst is 60:1.
[0387] A method for preparing a cycloolefin copolymer, comprising the following steps:
[0388] (1) Preparation of raw materials:
[0389] Organic solvent: cycloheptane;
[0390] Cyclic olefins: tetracyclododecene;
[0391] Acyclic olefins: 1-heptene;
[0392] The above-mentioned catalytic system for preparing cycloolefin copolymers includes a main catalyst, a co-catalyst and a chain transfer agent;
[0393] The pressure is 1 atm;
[0394] Methanol;
[0395] Acidified precipitant: The acid is hydrochloric acid and the precipitant is methanol;
[0396] (2) Under the protection of helium, an organic solvent, a cyclic olefin, a non-cyclic olefin, a chain transfer agent, a co-catalyst, and then a main catalyst are added to the reaction vessel in sequence, and the copolymerization reaction is carried out at 50 °C for 5 min. After the reaction is completed, methanol is added to terminate the polymerization;
[0397] The molar ratio of the organic solvent to the cyclic olefin is 13:1; the molar ratio of the cyclic olefin to the non-cyclic olefin is 8:1; the molar ratio of the cyclic olefin to the chain transfer agent is 67:1;
[0398] (3) pouring the reaction solution obtained from the polymerization reaction in step (2) into a container containing an acidified precipitant, and then filtering, washing with methanol three times, and vacuum drying in sequence to obtain a cycloolefin copolymer;
[0399] The vacuum degree of vacuum drying is 0.02 atm, the temperature is 60 °C, and the time is 8 hours.
[0400] The weight average molecular weight of the cycloolefin copolymer finally obtained was 8.5×10 3 g / mol, molecular weight distribution is 2.0, and polymerization activity is 9.5×10 8 g mol -1 , the glass transition temperature is 102 ℃, and the cycloolefin insertion rate is 38.40 mol%.
[0401] Embodiment 14
[0402] A catalytic system for preparing cycloolefin copolymers, comprising a main catalyst, a co-catalyst and a chain transfer agent;
[0403] The main catalyst is dimethylsilyl bridge group-(2,6-di(1,1,4,4-tetramethylcyclohexyl)fluorenyl)-tert-butylamino-dimethyltitanium;
[0404] The co-catalyst is triphenylcarbonium tetrakis(pentafluorophenyl)borate;
[0405] The chain transfer agent is di-n-butyl magnesium;
[0406] The molar ratio of the co-catalyst to the main catalyst is 5:1; the molar ratio of the chain transfer agent to the main catalyst is 300:1.
[0407] A method for preparing a cycloolefin copolymer, comprising the following steps:
[0408] (1) Preparation of raw materials:
[0409] Organic solvent: n-pentane;
[0410] Cycloolefins: cyclopentadiene;
[0411] Acyclic olefins: ethylene;
[0412] The above-mentioned catalytic system for preparing cycloolefin copolymers includes a main catalyst, a co-catalyst and a chain transfer agent;
[0413] Ethylene gas at a pressure of 3 atm;
[0414] Methanol;
[0415] Acidified precipitant: The acid is hydrochloric acid and the precipitant is ethanol;
[0416] (2) Under nitrogen protection, organic solvent, cycloolefin, chain transfer agent, and co-catalyst were added to the reaction vessel in sequence, acyclic olefin was introduced, and then the main catalyst was added. The copolymerization reaction was then carried out at 60 °C for 4 min. After the reaction was completed, methanol was added to terminate the polymerization.
[0417] The molar ratio of the organic solvent to the cyclic olefin is 16:1; the molar ratio of the cyclic olefin to the non-cyclic olefin is 10:1; the molar ratio of the cyclic olefin to the chain transfer agent is 74:1;
[0418] (3) pouring the reaction solution obtained from the polymerization reaction in step (2) into a container containing an acidified precipitant, and then filtering, washing with ethanol twice, and vacuum drying in sequence to obtain a cycloolefin copolymer;
[0419] The vacuum degree of vacuum drying is 0.03 atm, the temperature is 65 °C, and the time is 8 hours.
[0420] The weight average molecular weight of the cycloolefin copolymer finally obtained was 9.4×10 3 g / mol, molecular weight distribution is 1.9, polymerization activity is 8.9×10 8 g mol -1 , the glass transition temperature is 110 ℃, and the cycloolefin insertion rate is 40.00 mol%.
[0421] Embodiment 15
[0422] A catalytic system for preparing cycloolefin copolymers, comprising a main catalyst, a co-catalyst and a chain transfer agent;
[0423] The main catalyst is dimethylsilyl bridge group-fluorenyl-(α-dimethylnaphthylamino)-dimethyltitanium;
[0424] The co-catalyst is diethylaluminum chloride;
[0425] The chain transfer agent is dimethyl zinc;
[0426] The molar ratio of the co-catalyst to the main catalyst is 800:1; the molar ratio of the chain transfer agent to the main catalyst is 100:1.
[0427] A method for preparing a cycloolefin copolymer, comprising the following steps:
[0428] (1) Preparation of raw materials:
[0429] Organic solvent: cycloheptane;
[0430] Cyclic olefins: tetracyclododecene;
[0431] Acyclic olefins: propylene;
[0432] The above-mentioned catalytic system for preparing cycloolefin copolymers includes a main catalyst, a co-catalyst and a chain transfer agent;
[0433] Propylene gas at a pressure of 2 atm;
[0434] Methanol;
[0435] Acidified precipitant: The acid is hydrochloric acid and the precipitant is isopropanol;
[0436] (2) Under the protection of helium, an organic solvent, a cyclic olefin, a chain transfer agent, and a co-catalyst are sequentially added into the reaction vessel, a non-cyclic olefin is introduced, and then a main catalyst is added, and then a copolymerization reaction is carried out at 80 °C for 10 min. After the reaction is completed, methanol is added to terminate the polymerization;
[0437] The molar ratio of the organic solvent to the cyclic olefin is 23:1; the molar ratio of the cyclic olefin to the non-cyclic olefin is 4:1; the molar ratio of the cyclic olefin to the chain transfer agent is 54:1;
[0438] (3) pouring the reaction solution obtained from the polymerization reaction in step (2) into a container containing an acidified precipitant, followed by filtering, washing with isopropanol five times, and vacuum drying to obtain a cycloolefin copolymer;
[0439] The vacuum degree of vacuum drying is 0.01 atm, the temperature is 70 °C, and the time is 10 hours.
[0440] The weight average molecular weight of the cycloolefin copolymer finally obtained was 2.1×10 4 g / mol, molecular weight distribution is 2.6, and polymerization activity is 3.2×10 7 g mol -1 , the glass transition temperature is 85 ℃, and the cycloolefin insertion rate is 33.90 mol%.
[0441] Example 16
[0442] A catalytic system for preparing cycloolefin copolymers, comprising a main catalyst, a co-catalyst and a chain transfer agent;
[0443] The main catalyst is dimethylsilyl bridge group-(3,6-di-tert-butylfluorenyl)-tert-butylamino-dimethylzirconium;
[0444] The co-catalyst is trityl tetrakis(pentafluorophenyl)borate;
[0445] The chain transfer agent is n-butyl ethyl magnesium;
[0446] The molar ratio of the co-catalyst to the main catalyst is 1:1; the molar ratio of the chain transfer agent to the main catalyst is 200:1.
[0447] A method for preparing a cycloolefin copolymer, comprising the following steps:
[0448] (1) Preparation of raw materials:
[0449] Organic solvent: n-pentane;
[0450] Cycloolefins: cyclopentadiene;
[0451] Acyclic olefins: 1-hexene;
[0452] The above-mentioned catalytic system for preparing cycloolefin copolymers includes a main catalyst, a co-catalyst and a chain transfer agent;
[0453] The pressure is 1 atm;
[0454] Methanol;
[0455] Acidified precipitant: The acid is hydrochloric acid and the precipitant is ethanol;
[0456] (2) Under nitrogen protection, an organic solvent, a cyclic olefin, a non-cyclic olefin, a chain transfer agent, a co-catalyst, and then a main catalyst are added to the reaction vessel in sequence, and then a copolymerization reaction is carried out at 100 °C for 30 min. After the reaction is completed, methanol is added to terminate the polymerization;
[0457] The molar ratio of the organic solvent to the cyclic olefin is 11:1; the molar ratio of the cyclic olefin to the non-cyclic olefin is 2:1; the molar ratio of the cyclic olefin to the chain transfer agent is 5.4:1;
[0458] (3) pouring the reaction solution obtained from the polymerization reaction in step (2) into a container containing an acidified precipitant, and then filtering, washing with acetone once, and vacuum drying in sequence to obtain a cycloolefin copolymer;
[0459] The vacuum degree of vacuum drying is 0.06 atm, the temperature is 60 °C, and the time is 9 hours.
[0460] The weight average molecular weight of the cycloolefin copolymer finally obtained was 4.2×10 4 g / mol, molecular weight distribution is 2.4, and polymerization activity is 5.6×10 7 g mol -1 , the glass transition temperature is 90 ℃, and the cycloolefin insertion rate is 34.40 mol%.
Claims
1. A catalytic system for preparing cycloolefin copolymers, characterized in that: Including main catalyst, co-catalyst and chain transfer agent; The main catalyst is a silane-bridged fluorenylamino dimethyl titanium complex, a silane-bridged fluorenylamino dimethyl zirconium complex, a silane-bridged fluorenylamino dimethyl hafnium complex or a silane-bridged fluorenylamino dichloro hafnium complex; The co-catalyst is an aluminum compound co-catalyst or a boron compound co-catalyst; The chain transfer agent is one or more of the second main / sub-group metal complexes; The molar ratio of the aluminum compound co-catalyst to the main catalyst is 1-1000:1; the molar ratio of the boron compound co-catalyst to the main catalyst is 1-10:1; and the molar ratio of the chain transfer agent to the main catalyst is 1-500:
1.
2. A catalytic system for preparing cycloolefin copolymers according to claim 1, characterized in that: The main catalyst is methylphenylsilicon bridge group-(2,7-di-tert-butylfluorenyl)-(α-dimethylnaphthylamino)-dimethyltitanium, diphenylsilicon bridge group-(2,7-di-tert-butylfluorenyl)-(α-dimethylnaphthylamino)-dimethyltitanium, dimethylsilicon bridge group-fluorenyl-tert-butylamino-dimethyltitanium, dimethylsilicon bridge group-(2,7-di-tert-butylfluorenyl)-tert-butylamino-dimethyltitanium, dimethylsilicon bridge group-(3,6-di-tert-butylfluorenyl)-tert-butylamino-dimethyltitanium, dimethylsilicon bridge group-(3,6-dimethoxyfluorenyl)-tert-butylamino-dimethyltitanium, dimethylsilicon bridge group-(2,6-bis(1,1,4,4-tetramethylcyclohexyl)fluorenyl)-tert-butylamino-dimethyltitanium, dimethylsilicon bridge group-fluorenyl-(α-dimethylanilino) )-dimethyltitanium, dimethylsilyl bridge group-(2,7-di-tert-butylfluorenyl)-(α-dimethylanilino)-dimethyltitanium, dimethylsilyl bridge group-(3,6-di-tert-butylfluorenyl)-(α-dimethylanilino)-dimethyltitanium, dimethylsilyl bridge group-(3,6-dimethoxyfluorenyl)-(α-dimethylanilino)-dimethyltitanium, dimethylsilyl bridge group-(2,6-bis(1,1,4,4-tetramethylcyclohexyl)fluorenyl)-(α-dimethylanilino)-dimethyltitanium, dimethylsilyl bridge group-fluorenyl-(α-dimethylnaphthylamino)-dimethyltitanium, dimethylsilyl bridge group-(2,7-di-tert-butylfluorenyl)-(α-dimethylnaphthylamino)-dimethyltitanium, dimethylsilyl bridge group-(3,6-di-tert-butylfluorenyl)-(α-di methylnaphthylamino)-dimethyltitanium, dimethylsilyl bridge-(3,6-dimethoxyfluorenyl)-(α-dimethylnaphthylamino)-dimethyltitanium, dimethylsilyl bridge-(2,6-bis(1,1,4,4-tetramethylcyclohexyl)fluorenyl)-(α-dimethylnaphthylamino)-dimethyltitanium, dimethylsilyl bridge-fluorenyl-adamantylamino-dimethyltitanium, dimethylsilyl bridge-(2,7-di-tert-butylfluorenyl)-adamantylamino-dimethyltitanium, dimethylsilyl bridge-(3,6-di-tert-butylfluorenyl)-adamantylamino-dimethyltitanium, dimethylsilyl bridge-(3,6-dimethoxyfluorenyl)-adamantylamino-dimethyltitanium, dimethylsilyl bridge-(2,6-bis(1,1,4,4-tetramethylcyclohexyl)fluorenyl)-adamantylamino- Dimethyltitanium, dimethylsilyl-fluorenyl-tert-butylamino-zirconium dimethyl, dimethylsilyl-(2,7-di-tert-butylfluorenyl)-tert-butylamino-zirconium dimethyl, dimethylsilyl-(3,6-di-tert-butylfluorenyl)-tert-butylamino-zirconium dimethyl, dimethylsilyl-(3,6-dimethoxyfluorenyl)-tert-butylamino-zirconium dimethyl, dimethylsilyl-(2,6-bis(1,1,4,4-tetramethylcyclohexyl)fluorenyl)-tert-butylamino-zirconium dimethyl, dimethylsilyl-fluorenyl-adamantylamine-zirconium dimethyl, dimethylsilyl-(2,7-di-tert-butylfluorenyl)-adamantylamine-zirconium dimethyl, dimethylsilyl-(3,6-di-tert-butylfluorenyl)-adamantylamine-zirconium dimethyl, dimethylsilyl-(3,6-dimethoxyfluorenyl)-adamantylamine-dimethylzirconium, dimethylsilyl-(2,6-bis(1,1,4,4-tetramethylcyclohexyl)fluorenyl)-adamantylamine-dimethylzirconium, dimethylsilyl-fluorenyl-tert-butylamino-dimethylhafnium, dimethylsilyl-fluorenyl-tert-butylamino-dimethylhafnium, dimethylsilyl-fluorenyl-tert-butylamino-dichlorohafnium or dimethylsilyl-fluorenyl-adamantylamine-dichlorohafnium.
3. A catalytic system for preparing cycloolefin copolymers according to claim 1, characterized in that: The aluminum compound co-catalyst is one or more of methylaluminoxane, modified methylaluminoxane, trialkylaluminum, dialkylaluminum chloride, monoalkylaluminum dichloride and trialkylaluminum trichloride; the boron compound co-catalyst is one or more of N, N-dimethylanilinium tetrakis(pentafluorophenyl)borate, N, N-diethylanilinium tetrakis(pentafluorophenyl)borate, N, N-di(hexadecyl)anilinium tetrakis(pentafluorophenyl)borate, tris(pentafluorophenyl)borate, triphenylcarbonium tetrakis(pentafluorophenyl)borate and trityltetrakis(pentafluorophenyl)borate.
4. A catalytic system for preparing cycloolefin copolymers according to claim 1, characterized in that: The chain transfer agent is one or more of diphenyl zinc, dimethyl zinc, diethyl zinc, diisopropyl zinc, dibutyl zinc, diethyl magnesium, diisobutyl magnesium, di-n-butyl magnesium and n-butylethyl magnesium.
5. A method for preparing a cycloolefin copolymer, characterized in that: The catalytic system according to any one of claims 1 to 4 is used to copolymerize cycloolefins and non-cyclic olefins under the catalytic action thereof to obtain cycloolefin copolymers.
6. The method for preparing a cycloolefin copolymer according to claim 5, characterized in that: Cycloolefins are unsaturated cyclic olefins with the following structural formula: ; In the formula, m is 0, 1 or 2, and R2 and R3 are each independently selected from a hydrogen atom, an alkyl group and a cycloalkyl group; Acyclic olefins are C2~C20 straight-chain olefins with the following structural formula: ; In the formula, R1 is independently hydrogen or a saturated aliphatic hydrocarbon group having 1 to 19 carbon atoms.
7. The method for preparing a cycloolefin copolymer according to claim 5, characterized in that: The reaction adopts a solution polymerization method and the copolymerization reaction is carried out in an organic solvent; the organic solvent is one or more of aromatic hydrocarbons, aliphatic hydrocarbons and alicyclic hydrocarbons.
8. The method for preparing a cycloolefin copolymer according to claim 7, characterized in that: The reaction temperature is 40~120 ℃; the reaction time is 1~30 min.
9. The method for preparing a cycloolefin copolymer according to claim 5, characterized in that: The molar ratio of the cyclic olefin to the non-cyclic olefin is 1 to 10:
1.
10. The method for preparing a cycloolefin copolymer according to any one of claims 5 to 9, characterized in that: The weight average molecular weight of the cycloolefin copolymer is 1×10 3 ~60×10 4 g / mol, molecular weight distribution is 1.5~3.0, polymerization activity is 1×10 7 ~5×10 8 g mol -1 h -1 , the glass transition temperature is 67~147 ℃, and the cycloolefin insertion rate is 21.0~51.1 mol%.
11. A cycloolefin copolymer prepared by the preparation method according to any one of claims 5 to 10, characterized in that: The structural formula is as follows: ; Among them, 1≤X / Y≤5, 2≤n≤5000; R1 is independently hydrogen or a saturated aliphatic hydrocarbon group having 1 to 19 carbon atoms; R2 and R3 are each independently selected from a hydrogen atom, an alkyl group and a cycloalkyl group.
Citation Information
Patent Citations
Preparation method of cycloolefin copolymer
CN109593160A
Functional cyclic olefin copolymer and preparation method thereof
CN106336482A
Rare earth metallocene composition containing heterocyclic structure and application of composition
CN109369836A
Polymerization method for efficiently regulating and controlling molecular weight of cycloolefin copolymer through reversible coordination chain transfer
CN112812211A
Ethylene / alpha-olefin random copolymer for photovoltaic adhesive film and application of ethylene / alpha-olefin random copolymer
CN117567961A
Cited By
Cycloolefin copolymer as well as preparation method and application thereof
CN120795236A